Functionalization of polymers using an atmospheric plasma jet in a fluidized bed reactor and its impact on selective laser melting processes - Sachs, Marius; Schmitt, Adeliene; Schmidt, Jochen; Peukert, Wolfgang; Wirth, Karl-Ernst (11th International Conference on Fluidized Bed Technology, CFB 2014, 2014)
In order to improve thermoplastic particles (e.g. Polyamide, Polypropylene and Polyethylene) for Selective Laser Melting (SLM) processes a new approach for functionalization of temperature-sensitive polymer powders at large scales is investigated. This is achieved by combining an atmospheric pressure plasma jet and a fluidized bed reactor. Using pressurized air as plasma gas, radicals including OH* are generated. The functionalization leads to an increase of surface energy of the treated polymer powder without changing the bulk properties. Application of the functionalized polymers in a SLM process to build single layers leads to an improvement of the melted layer
Keywords: Atmospheric pressure plasma jet; Polymer functionalization; Fluidized bed reactor